Economic analysis of accident law - Shavell, Steven, 1946- (Harvard University Press, 1987)
Accident law, if properly designed, is capable of reducing the incidence of mishaps by making people act more cautiously. Scholarly writing on this branch of law traditionally has been concerned with examining the law for consistency with felt notions of right and duty. Since the 1960s, however, a group of legal scholars and economists have focused on identifying the effects of accident law on people's behavior. Steven Shavell's book is the definitive synthesis of research to date in this new field.